DAMPAK COVID-19 TERHADAP SOSIAL EKONOMI PEDAGANG PASAR TRADISIONAL, STUDI KASUS: PASAR WAGE, KABUPATEN BANYUMAS - Bayu Setiarto; Anang Widhi Nirwansyah (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
This study focuses on investigating the impact of the Covid-19 pandemic on the socio-economic conditions of traders in the Wage Market located in the Banyumas district of Indonesia, specifically in the city of Purwokerto. The Covid-19 outbreak in 2020 brought about significant social and economic challenges worldwide, including within local economies. Indonesia, like many other regions, experienced widespread social and economic transformations as a result. The objective of this research is to examine the specific changes in socio-economic conditions faced by traders at the Wage Market due to the Covid-19 pandemic. To achieve this, a qualitative research method will be employed, involving interviews with traders in the market. These interviews will be supplemented with data collection, including photographs taken during the interviews. The collected data will be carefully processed and analyzed, incorporating insights from reliable sources within the Pasar Wage. Through the findings obtained from the interviews, this study will shed light on the precise impact of Covid-19 on the socio-economic conditions of traders in the Pasar Wage. By exploring the experiences and perspectives of these traders, it aims to provide a deeper understanding of the challenges faced by local businesses in the wake of the pandemic.